2008
DOI: 10.1177/1753425908093932
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induces the production of tumor necrosis factor-α in RAW 264.7 macrophage cells via activation of p38 and stress-activated protein kinase

Abstract: The effect of hydrogen peroxide (H(2)O(2)) on production of tumor necrosis factor (TNF)-alpha was examined in RAW 264.7 murine macrophage cells. H(2)O( 2) led to production of TNF-alpha up to 24 h after the treatment, but not nitric oxide in RAW 264.7 cells. H(2)O(2) induced TNF-alpha production in mouse peritoneal macrophages as well as RAW 264.7 cells. The H(2)O(2)induced TNF-alpha production was prevented by inhibitors of p38 and stress-activated protein kinase (SAPK/JNK), and H(2)O( 2) induced the phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…The role of ROS in FSHD is well reported, and our FSHD network contains many genes in the ROS-mediated pathway, including TNF-a. DUX4 represses genes of the glutathione redox pathway, likely causing ROS accumulation in FSHD muscle [45], which may lead to increased TNF-a as part of a pro-inflammatory response [46]. Additionally, levels of TNF-a are negatively correlated with muscle endurance [42].…”
Section: Discussionmentioning
confidence: 99%
“…The role of ROS in FSHD is well reported, and our FSHD network contains many genes in the ROS-mediated pathway, including TNF-a. DUX4 represses genes of the glutathione redox pathway, likely causing ROS accumulation in FSHD muscle [45], which may lead to increased TNF-a as part of a pro-inflammatory response [46]. Additionally, levels of TNF-a are negatively correlated with muscle endurance [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, activation of MAPKs (JNK, p38, ERK) is differentially regulated by cleavage size (40 kDa and 36 kDa) of mammalian sterile 20-like kinase 1, which is controlled by caspase-7 and -3 [50] . ASK1-induced and ROS-dependent activation of MAPKs is crucial for apoptosis [43,51] , and for TLR4-mediated mammalian innate immunity [52] . In the case of oxidative stress, a positive feedback may form in the ASK1-p38-TNF-α pathway, which enhances ROS-mediated apoptosis (Figure 2).…”
Section: Ros Involve Apoptosis That Relates To the P38 Pathwaymentioning
confidence: 99%
“…It has been shown that concentrations of TNF- α released from LPS-stimulated cells increased significantly [23]. Hydrogen peroxide induced TNF- α production in macrophages via activating p38 as oxidative stress-related signal pathways [24]. After vitamin C treatment, a significant decrease in TNF- α , P38, and p-P38 in LPS-stimulated cells was observed in present study (Figure 4(e), P = 0.001 and 0.0006).…”
Section: Resultsmentioning
confidence: 99%